Spatio-Temporal Characteristics of Inhibition Mapped by Optical Stimulation in Mouse Olfactory Bulb - Lehmann, Alexander; D’Errico, Anna; Vogel, Martin; Spors, Hartwig (Frontiers in Neural Circuits, 2016)
Mitral and tufted cells (MTCs) of the mammalian olfactory bulb are connected via dendrodendritic synapses with inhibitory interneurons in the external plexiform layer. The range, spatial layout, and temporal properties of inhibitory interactions between MTCs mediated by inhibitory interneurons remain unclear. Therefore, we tested for inhibitory interactions using an optogenetic approach. We optically stimulated MTCs expressing channelrhodopsin-2 in transgenic mice, while recording from individual MTCs in juxtacellular or whole-cell configuration in vivo. We used a spatial noise stimulus for mapping interactions between MTCs belonging to different glomeruli in the dorsal bulb. Analyzing firing responses of MTCs to the stimulus, we did not find robust lateral inhibitory effects that were spatially specific. However, analysis of sub-threshold changes in the membrane potential revealed evidence for inhibitory interactions between MTCs that belong to different glomerular units. These lateral inhibitory effects were short-lived and spatially specific. MTC response maps showed hyperpolarizing effects radially extending over more than five glomerular diameters. The inhibitory maps exhibited non-symmetrical yet distance-dependent characteristics.